Vocalization thresholds related to noxious paw pressure are decreased by paradoxical sleep deprivation and increased after sleep recovery in rat - Onen, S.Hakki; Alloui, Abdelkrim; Eschalier, Alain; Dubray, Claude (Neuroscience letters, 2000)
The aim of this study was to assess the effect of paradoxical sleep deprivation (PSD) and sleep recovery on the vocalization threshold in rats submitted to a mechanical noxious stimulus. Sixteen male Wistar rats were randomly assigned in two groups: controls (n=8), paradoxical sleep deprived rats (n=8). PSD was performed using the 'inverted flower pot' technique. Paw pressure test was used to assess the sensitivity to mechanical noxious stimulus (vocalization threshold). The experiment was divided into three periods: baseline (day 1, day 2), PSD (day 3, day 4, day 5) and recovery (day 6, day 7, day 8, day 9). After 48 and 72 h of PSD, the vocalization thresholds decreased significantly in comparison to the control rats (day 4: 245+/-21 vs. 303+/-20 g, P=0.05; day 5: 256+/-17 vs. 324+/-22 g, P=0.02). In PSD group, relative to controls, vocalization thresholds increased significantly after 48, 72, and 96 h of recovery sleep periods (day 7: 378+/-24 vs. 307+/-8 g P=0.01; day 8: 384+/-27 vs. 316+/-23 g, P=0.02; day 9: 395+/-24 vs. 328+/-15 g, P=0.02). Vocalization thresholds on day 6 were not significantly different in both groups (375+/-20 vs. 324+/-24 g, P=0.08). In conclusion, experimental PSD in rats induces a significant decrease in vocalization threshold to mechanical noxious stimulus, which is totally reversed during the sleep recovery period.